An excitatory reflex between R1 and R2 responses of the blink reflex to supraorbital nerve stimuli. Issue 3 (March 2016) - Leon, L.; Cabib, C.; Cordoso, M.; Motta, I.; Valls-Solé, J.
Abstract : Background: The typical pattern of the blink reflex to ipsilateral electrical stimuli to the supraorbital nerve (SN) is composed by an early, short duration, well synchronized, R1 response and a late, long duration, polyphasic R2 response. We examined whether the period between R1 and R2 results from lack of excitatory inputs or active inhibition. Methods: Tests were performed in 5 healthy subjects and 10 patients of various disorders affecting blink reflex excitability, including postparalytic facial syndrome and hemifacial spasm. All subjects wore surface electrodes attached to the orbicularis oculi and stimuli were applied to the SN. After obtaining the conventional blink reflex, healthy subjects were requested to close their eyes at various levels of force while applying again the same stimulus. Results: In healthy subjects closing the eyes with force, SN stimulation induced a response of smaller amplitude and shorter latency than the R2 (25.2 ± 1.3 ms). A short and incomplete silent period emerged after R1 and after R2. Patients with postparalytic facial syndrome and essential hemifacial spasm showed activity interfering with the silence between R1 and R2, with often expanding between the two responses, repeating in successive trials. Conclusions: Our results show that there can be reflex responses between R1 and R2 in healthy subjects during contraction and in patients with abnormal reflex excitability. This suggests that the absence of activity between the two responses in normal conditions is the consequence of an active inhibition that reaches the facial motoneurons at that point.